FOXM1 Is an Oncogenic Mediator in Ewing Sarcoma - Christensen, Laura (Public Library of Science, 2013)
Ewing Family Tumors (Ewing Sarcoma and peripheral Primitive Neuroectodermal Tumor) are common bone and soft tissue malignancies of childhood, adolescence and young adulthood. Chromosomal translocation in these tumors produces fusion oncogenes of the EWS/ETS class, with EWS/FLI1 being by far the most common. EWS/ETS chimera are the only well established driver mutations in these tumors and they function as aberrant transcription factors. Understanding the downstream genes whose expression is modified has been a central approach to the study of these tumors. FOXM1 is a proliferation associated transcription factor which has increasingly been found to play a role in the pathogenesis of a wide range of human cancers. Here we demonstrate that FOXM1 is expressed in Ewing primary tumors and cell lines. Reduction in FOXM1 expression in Ewing cell lines results in diminished potential for anchorage independent growth. FOXM1 expression is enhanced by EWS/FLI1, though, unlike other tumor systems, it is not driven by expression of the EWS/FLI1 target GLI1. Thiostrepton is a compound known to inhibit FOXM1 by direct binding. We show that Thiostrepton diminishes FOXM1 expression in Ewing cell lines and this reduction reduces cell viability through an apoptotic mechanism. FOXM1 is involved in Ewing tumor pathogenesis and may prove to be a useful therapeutic target in Ewing tumors.